Effectiveness of digital versus printed Arabic text on the literacy mathematics tasks of seventh- and eighth-grade students - Abd Algani, Yousef; Gross, Zehavit (Research Journal in Advanced Humanities, 2024)
Studies have demonstrated that use of digital rather than printed texts improve student literacy (reading comprehension of Problem solving in mathematics) and boosts motivation. The current study examines the effectiveness of digital versus printed media on the literacy of seventh- and eighth graders in Arab schools in Israel. This is the first time this topic has been examined in this setting. The study uses a quantitative methodology that involved 132 students and 77 teachers from middle-schools in the Arab sector in Israel. Two questionnaires, the first for students and the second for teachers were distributed and the data were analyzed using SPSS. The results reveal that both seventh- and eighth-grade students perform better using digital rather than printed material. No discernible gender difference was found.